1999
DOI: 10.1111/j.1348-0421.1999.tb01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Expansion of Pneumococcal Colonization from the Nose to the Lower Respiratory Tract in Mice Preinfected with Influenza Virus

Abstract: A strain of Streptococcus pneumoniae, when inoculated intranasally in 2 μl of suspension into BALB/c mice preinfected with influenza virus, colonized first in the nose, and several days thereafter also colonized significantly in the trachea and lungs with purulent inflammation. Pneumoccocal colonization was also observed in the noses of normal mice after the same bacterial inoculation, but not apparently in the lower respiratory tract. These results suggest that pneumococcal infection may develop from the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…We found that susceptibility to S. pneumoniae was the greatest at 6 days after influenza infection and was not increased at 3 days after influenza infection. Several other groups have found similar results, and clinical evidence supports this timeframe for maximum susceptibility (14,24,42,59). Influenza-induced tissue damage is greatest after 6 days of influenza infection (44), and Plotkowski et al found that adherence of S. pneumoniae to influenza-infected tracheas was greatest after 6 days of influenza infection (48).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We found that susceptibility to S. pneumoniae was the greatest at 6 days after influenza infection and was not increased at 3 days after influenza infection. Several other groups have found similar results, and clinical evidence supports this timeframe for maximum susceptibility (14,24,42,59). Influenza-induced tissue damage is greatest after 6 days of influenza infection (44), and Plotkowski et al found that adherence of S. pneumoniae to influenza-infected tracheas was greatest after 6 days of influenza infection (48).…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have found that susceptibility to S. pneumoniae infection is greatest at 6 to 7 days after influenza infection (14,24,42,59). To validate our coinfection model, S. pneumoniae was inoculated into noninfected mice or mice infected with influenza for 3 or 6 days, and S. pneumoniae growth over 12 and 24 h was measured to determine when susceptibility to S. pneumoniae infection was greatest.…”
Section: Resultsmentioning
confidence: 99%
“…Co-infection of influenza A with S. pneumoniae resulted in severe morbidity with a 75% death rate within 40 h, clear evidence of the consequences of co/secondary bacterial infection (Berendt et al, 1975). These findings are reflected in several other studies, with some even showing that co-infection may assist in the spreading of S. pneumoniae infection to the lower respiratory tract (Takase et al, 1999; Seki et al, 2004). …”
Section: Pathobionts Associated With Co/secondary Bacterial Infectionsupporting
confidence: 59%
“…The trachea is thought to play a role in the progression of S. pneumoniae from the nasal mucosa, where it asymptomatically colonizes the nasal epithelium, to the lungs, resulting in pneumonia (15,44). Changes to the tracheal epithelium induced by influenza virus may increase susceptibility to a secondary S. pneumoniae infection by increasing pneumococcal adherence to the tracheal epithelium and/or decreasing the clearance of S. pneumoniae via the mucociliary escalator of the trachea, because many of the ciliated cells are destroyed (15,24).…”
Section: Discussionmentioning
confidence: 99%